Web-Based Decision Support System for New Business Location Selection Using the Analytical Hierarchy Process (AHP) Method - Muhamad Aldy Akbar; Muhammad Ali Akbar (Journal of Creative Power and Ambition (JCPA), 2026)
Business location selection is a strategic decision for a digital printing business because it affects operating costs, customer accessibility, and proximity to target markets. Previous studies on business location selection have generally focused on alternative ranking and have rarely integrated AHP weighting, dynamic spatial information, competitor data, sensitivity analysis, and usability evaluation within one application. This study developed a web-based Decision Support System (DSS) for selecting shop-house locations for a digital printing business in East Jakarta using the Analytical Hierarchy Process (AHP). The six criteria were rental price, building area, road accessibility, parking availability, surrounding population density, and proximity to schools, universities, offices, or government institutions. The study used six shop-house alternatives from 99.co, official East Jakarta population data, nearby facilities from OpenStreetMap through the Overpass API and OSRM, and competitor data obtained by scraping Google Maps. Pairwise comparison questionnaires were completed by 36 respondents and combined using the geometric mean. The group Consistency Ratio was 0.0197, indicating a consistent comparison matrix. The highest weights were assigned to surrounding population density (34.55%), proximity to facilities (23.68%), and road accessibility (18.64%). Alternative A5 in Matraman ranked first with a final score of 0.919 and was categorized as highly recommended. Functional testing showed that all main features operated as designed, while usability testing with 20 respondents produced an average System Usability Scale (SUS) score of 81.5, categorized as very good. These findings indicate that the system can help users compare shop-house locations more objectively, systematically, and understandably